Bluetooth an enabler for personal area networking. - Johansson, P.
We find ourselves today often carrying numerous portable electronic devices, such as notebook computers, mobile phones, PDAs, digital cameras, and mp3/MD/DVD players, used to help and entertain us in our professional as well as private lives. For the most part, these devices are used separately, and their applications do not interact. Imagine, however, if they could interact directly and thus create a network where information may flow seamlessly between the devices-such a network of personal devices is often referred to as a personal area network, or PAN. Moreover, access to the Internet via a (public) wireless LAN access point and/or via a 3G UMTS mobile phone would enable the PAN to be constantly online. The strongest candidate to provide the cheap short-range radio links necessary to enable such networks is the Bluetooth wireless technology. Seen from a networking perspective, a PAN will be expected to have participants, both of its ?own? devices and ?guest? devices from other PANs, continuously moving in and out of its coverage. To cope with this volatile nature of the network, the concept of ad hoc networking may be applied to create robust and flexible connectivity. A major technical step is taken when the Bluetooth piconet network architecture, a strict star topology, is extended into a scatternet architecture, where piconets are interconnected. A consequence of creating scatternet-based PANs is that some nodes will form gateways between piconets, and these gateways must be capable of time sharing their presence In each piconet of which they are members. While the Bluetooth standard defines the gateway nodes, the actual mechanisms and algorithms that accomplish the interpiconet scheduling (IPS) are left rather open. Given the lack of research literature in the subject, an overall architecture for handling scheduling in a scatternet is presented. A family of feasible IPS algorithms, referred to as rendezvous point algorithms, is also introduced and discussed
Keywords: 3G UMTS mobile phone; Bluetooth piconet network architecture; Bluetooth standard; Bluetooth wireless technology; IPS algorithms; Internet access; PAN; PDA; Ad hoc networking; Digital cameras; Gateway nodes; Interpiconet scheduling; Mobile phones; Mp3/MD/DVD players; Network nodes; Notebook computers; Packet forwarding; Personal area networking; Piconet interconnection; Portable electronic devices; Public wireless LAN; Rendezvous point algorithms; Scatternet architecture; Scatternet scheduling; Short-range radio links; Star topology; Time sharing